Urban Sustainability and Justice Just Sustainabilities and Environmental Planning - Broto, Vanesa Castán (Just Sustainabilities, 2019)
Urban Sustainability and Justice presents an innovative yet practical approach to incorporate equity and social justice into sustainable development in urban areas, in line with the commitments of the UN's Sustainable Development Goals and the New Urban Agenda. This open access work proposes a feminist reading of just sustainabilities' principles to reclaim sustainability as a progressive discourse which informs action on the ground. This work will help the committed activist (whether they are on the ground, working in a community, in a non-governmental organization (NGO), in a business, at a university, in any sphere in government) to connect their work to international efforts to deliver environmental justice in cities around the world. Drawing on a comparative, international analysis of sustainability initiatives in over 200 cities, Castán Broto and Westman find limited evidence of the implementation of just sustainabilities principles in practice, but they argue that there is considerable potential to develop a justice-oriented sustainability agenda. Highlighting current successes while also assessing prospects for the future, the authors show that just sustainabilities is not merely an aspirational discourse, but a frame of reference to support radical action on the ground. The eBook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by The University of Sheffield.